Wine and translation: an analysis of phraseological units in English and Spanish wine technical sheets. - Moreno-Pérez, Leticia; López-Arroyo, Belén (Perspectives: Studies in Translatology, 2025)
The language used to market and describe wine is characterised by the subjectivity and creativity of the terms used. This makes the encoding and decoding of oenology-related texts a demanding task. As genres in this field are persuasive in nature, the correct translation of wine-related terminology is crucial to sell the product. In wine-related genres, phraseological units have been understudied especially with regards to translation. The aim of this paper is to shed light on the use of phraseological units in one of the most representative genres in the field, i.e. wine technical sheets, with a view to assisting translators in the comprehension and management of oenology-related texts. A contrastive analysis was carried out using an English-Spanish comparable corpus in order to identify and classify phraseological units according to their function and semantic characteristics; further analysis of the distribution of these units allowed us to define the rhetorical structure of wine technical sheets. The study evidenced the high frequency and complexity of phraseological units in the genre.